2008
DOI: 10.1095/biolreprod.108.067686
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Markers of Oocyte Competence Expressed in Bovine Cumulus Cells Matured with Follicle-Stimulating Hormone and/or Phorbol Myristate Acetate In Vitro

Abstract: Oocyte competence is the ability of the oocyte to complete maturation, undergo successful fertilization, and reach the blastocyst stage. Cumulus cells are indispensable for this process. Their removal significantly affects the blastocyst rates. Moreover, the properties and functions of cumulus cells are regulated by the oocyte. They also reflect the oocyte's degree of maturation. Our study was aimed at identifying markers of oocyte competence that are expressed in bovine cumulus cells. In a previous study in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
170
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(187 citation statements)
references
References 98 publications
14
170
1
2
Order By: Relevance
“…In parallel, we and others have observed that granulosa/follicular gene expression may be associated with developmental competence of the enclosed oocyte in bovines (Robert et al 2001), rats (Jiang et al 2010), and humans (Assidi et al 2008, 2010, 2010. In our previous experiment, it was observed that an improved developmental rate was obtained with a hormonal treatment consisting of 3 days of stimulation using FSH plus a coasting period of 44 h (Blondin et al 2002).…”
Section: Introductionmentioning
confidence: 51%
“…In parallel, we and others have observed that granulosa/follicular gene expression may be associated with developmental competence of the enclosed oocyte in bovines (Robert et al 2001), rats (Jiang et al 2010), and humans (Assidi et al 2008, 2010, 2010. In our previous experiment, it was observed that an improved developmental rate was obtained with a hormonal treatment consisting of 3 days of stimulation using FSH plus a coasting period of 44 h (Blondin et al 2002).…”
Section: Introductionmentioning
confidence: 51%
“…Of the apoptosis related genes, CCDC80, COL1A1, CTGF, DNAJB1, LGALS9, LTF, LNM, MT2A, MTH11, SOX4, and TIMP2 showed significant differences in expression levels between the two age groups (Supplementary Table 2). Table 3 lists the marker genes for the largest healthy follicles and the subordinate follicles in cows [31][32][33][34][35][36][37], and shows the expression levels of these genes in aged and young cows. All genes associated with subordinate follicles were expressed at lower levels in young cows.…”
Section: Comparison Of Gene Expression In Granulosa Cells Of Young Anmentioning
confidence: 99%
“…Many pathways including cAMP and cAMP-dependent protein kinase A are reported to be involved in regulating this process (Downs et al, 2002;Homa, 1988). FSH stimulates germinal-vesicle breakdown (GVBD) and resumption of oocyte maturation both in vitro and in vivo (Assidi et al, 2008(Assidi et al, , 2010Sirard et al, 2007) through binding to FSH receptors on granulosa cells or cumulus cells which are G-protein-coupled receptors (Heitman and Ijzerman, 2008;Segaloff et al, 1990) and results in a signalling cascade involving increasing intracellular cAMP concentrations (Dekel, 1988) and stimulation of prostaglandin E synthesis (Shimada et al, 2006;Yamashita et al, 2011).…”
Section: Introductionmentioning
confidence: 99%